2009 34th International Conference on Infrared, Millimeter, and Terahertz Waves 2009
DOI: 10.1109/icimw.2009.5324686
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform in THz measurements of refractive index

Abstract: A Fourier Transform is applied to the coherent detection signal in the THz photomixer arrangement. The method is used in measurements of a refractive index of plastic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Continuous wave operation can be easily obtained with a terahertz photomixer -see Fig 1. It consists of two main optical arms: a pumping beam (a distance from a cubic beam splitter BS to a transmitting antenna Tx plus a tera− hertz part from Tx to a receiving antenna Rx), and a probing beam (a distance from a cubic beam splitter BS, via mirrors arrangement to a receiving antenna Rx) [9]. The signal trave− ling along the pumping arm excites carriers at the LT−GaAs photoconductive antenna.…”
Section: Continuous Wave Operationmentioning
confidence: 99%
“…Continuous wave operation can be easily obtained with a terahertz photomixer -see Fig 1. It consists of two main optical arms: a pumping beam (a distance from a cubic beam splitter BS to a transmitting antenna Tx plus a tera− hertz part from Tx to a receiving antenna Rx), and a probing beam (a distance from a cubic beam splitter BS, via mirrors arrangement to a receiving antenna Rx) [9]. The signal trave− ling along the pumping arm excites carriers at the LT−GaAs photoconductive antenna.…”
Section: Continuous Wave Operationmentioning
confidence: 99%
“…It has been shown that the THz technology is applicable to a non-destructive inspection of industrial goods and plastics [1,2] as well as in the semiconductor industry, homeland security [3], biology and medicine. The polymer industry is of a special interest, while many polymers and additives are transparent to the THz waves.…”
Section: Introductionmentioning
confidence: 99%